Influence of Health Insurance Expansion on Disparities in the Treatment of Acute Cholecystitis. Issue 1 (July 2015) - Loehrer, Andrew P.; Song, Zirui; Auchincloss, Hugh G.; Hutter, Matthew M.
Abstract : Objective: To evaluate the impact of the 2006 Massachusetts (MA) health reform on disparities in the management of acute cholecystitis (AC). Background: Immediate cholecystectomy has been shown to be the optimal treatment for AC, yet variation in care persists depending upon insurance status and patient race. How increased insurance coverage impacts these disparities in surgical care is not known. Methods: A cohort study of patients admitted with AC in MA and 3 control states from 2001 through 2009 was performed using the Hospital Cost and Utilization Project State Inpatient Databases. We examined all nonelderly white, black, or Latino patients by insurance type and patient race, evaluating changes in the probability of undergoing immediate cholecystectomy and disparities in receiving immediate cholecystectomy before and after Massachusetts health reform. Results: Data from 141, 344 patients hospitalized for AC were analyzed. Before the 2006 reform, government-subsidized/self-pay (GS/SP) patients had a 6.6 to 9.9 percentage-point lower ( P < 0.001) probability of immediate cholecystectomy in both MA control states. The MA insurance expansion was independently associated with a 2.5 percentage-point increased probability of immediate cholecystectomy for all GS/SP patients in MA ( P = 0.049) and a 5.0 percentage-point increased probability ( P = 0.011) for nonwhite, GS/SP patients compared to control states. Racial disparities in the probability of immediate cholecystectomy seen before health care reform were no longer statistically significant after reform in MA while persisting in control states. Conclusions: The MA health reform was associated with increased probability of undergoing immediate cholecystectomy for AC and reduced disparities in undergoing cholecystectomy by insurance status and patient race. Abstract : The 2006 Massachusetts health reform provides a unique natural experiment to evaluate the influence of expanded health care insurance on known disparities in the management of acute cholecystitis. Relative to concurrent trends in control states, the Massachusetts reform was independently associated with increased use of cholecystectomy and reduced disparities by both insurance status and patient race. The Massachusetts experience provides optimistic evidence for increased quality of care and decreased disparities in care for the management of acute cholecystitis, but additional evaluation is needed to assess the generalizability of the Massachusetts experience elsewhere in the country.